Economic impact of GM crops: The global income and production effects 1996–2012 - Brookes, Graham (GM Crops Food, 2014)
A key part of any assessment of the global value of crop biotechnology in agriculture is an examination of its economic impact at the farm level. This paper follows earlier annual studies which examined economic impacts on yields, key costs of production, direct farm income and effects, and impacts on the production base of the four main crops of soybeans, corn, cotton and canola. The commercialization of genetically modified (GM) crops has continued to occur at a rapid rate, with important changes in both the overall level of adoption and impact occurring in 2012. This annual updated analysis shows that there have been very significant net economic benefits at the farm level amounting to $18.8 billion in 2012 and $116.6 billion for the 17-year period (in nominal terms). These economic gains have been divided roughly 50% each to farmers in developed and developing countries. GM technology have also made important contributions to increasing global production levels of the four main crops, having added 122 million tonnes and 230 million tonnes respectively, to the global production of soybeans and maize since the introduction of the technology in the mid-1990s.